2007
DOI: 10.1111/j.1600-0889.2007.00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Annual cycle of methane emission from a boreal fen measured by the eddy covariance technique

Abstract: A B S T R A C TThe northern wetlands are one of the major sources of methane into the atmosphere. We measured annual methane emission from a boreal minerotrophic fen, Siikaneva, by the eddy covariance method. The average wintertime emissions were below 1 mg m −2 h −1 , and the summertime emissions about 3.5 mg m −2 h −1 . The water table depth did have any clear effect on methane emissions. During most of the year the emission depended on the temperature of peat below the water table. However, during the high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
220
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 247 publications
(251 citation statements)
references
References 40 publications
28
220
3
Order By: Relevance
“…8, bottom left). The regional inversions (Kim2011 and Winderlich2012) agreed on a July peak for CH 4 , although Winderlich2012 suggested a noticeably larger contribution from cold season months than the others (which is plausible, given reports of non-zero winter emissions; Rinne et al, 2007;Kim et al, 2007;Panikov and Dedysh, 2000). In contrast, both Bousquet inversions peaked in August.…”
Section: Average Seasonal Cyclesmentioning
confidence: 67%
See 1 more Smart Citation
“…8, bottom left). The regional inversions (Kim2011 and Winderlich2012) agreed on a July peak for CH 4 , although Winderlich2012 suggested a noticeably larger contribution from cold season months than the others (which is plausible, given reports of non-zero winter emissions; Rinne et al, 2007;Kim et al, 2007;Panikov and Dedysh, 2000). In contrast, both Bousquet inversions peaked in August.…”
Section: Average Seasonal Cyclesmentioning
confidence: 67%
“…Indeed, the paucity of long in situ records limited our ability to evaluate LPX-BERN's relatively low sensitivity to water table depth. Year-round observations would also be helpful, as winter emissions are sparsely sampled (Rinne et al, 2007;Kim et al, 2007;Panikov and Dedysh, 2000) and inversions disagree as to the magnitude of winter emissions (Fig. 8).…”
Section: Future Needs For Observations and Inversionsmentioning
confidence: 99%
“…The peat depth is a maximum 5.5 m (Mathijssen et al, 2016). More detailed site descriptions were presented in earlier work Rinne et al, 2007).…”
Section: Study Sitesmentioning
confidence: 99%
“…The Webb-Pearman-Leuning (WPL) correction (Webb et al, 1980) was applied when applicable (Laurila et al, 2005). More details of the measurement systems and data post-processing are given in previous studies (Aurela et al, 2009;Laurila et al, 2005;Lohila et al, 2016;Peltola et al, 2013;Rinne et al, 2007). For this study, the half-hourly averages were further averaged to daily fluxes to match the time resolution of the model.…”
Section: Field Measurementsmentioning
confidence: 99%
“…A good example is methane, a gas whose sensors have been able to estimate fluxes for over a decade and a gas long recognized to be an important part of the carbon cycle in peatlands (Gorham, 1991) and particularly influential to the greenhouse gas forcing of the climate. One of the first studies was that of Rinne et al (2007) in a boreal wetland fen, who made the significant observation that about 20 % of the annual CO 2 assimilated by plants was emitted as CH 4 . Petrescu et al (2015) used data from a network of wetland flux towers to estimate CO 2 and CH 4 fluxes and concluded that net radiative forcings from the two gases were much higher in wetlands converted to human uses.…”
Section: Fluxnet and Trace Gasesmentioning
confidence: 99%